Energy Drinks Consumption and Awareness Among Secondary School Students in Benghazi- Libya - Hajer Omar; Asma Omar; Aisha Muhammed; Mahmoud Elderbi (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and Objectives: Recently consumption of energy drinks has become popular among young people especially athletes and students. In this study we investigate the consumption frequency and pattern among secondary school students. Methods: 480 secondary school students were participated in this study. Data was gathered using a self-response questionnaire that mainly focused on the patterns of consumption and knowledge of the students about energy drinks effects among consumers. Results: Out of 480 students, 165 (34.38%) of the participants were consumers, while 315 (65.63%) were none consumers. The result showed that the majority of the consumers (65.63%) have adequate knowledge about physical and mental effects of energy drinks. However, 63.54%of them do not know the ingredients of the energy drinks. Conclusion: About one third of the participants were energy drinks consumers, most of them were not a regular consumer. Our study shows a good knowledge about energy drinks physical and mental effects among participants.